Pollen of common ragweed (Ambrosia artemisiifolia L.): Illumina-based de novo sequencing and differential transcript expression upon elevated NO2/O3. (May 2017) - Zhao, Feng; Durner, Jörg; Winkler, J. Barbro; Traidl-Hoffmann, Claudia; Strom, Tim-Matthias; Ernst, Dieter; Frank, Ulrike
Abstract: Common ragweed ( Ambrosia artemisiifolia L.) is a highly allergenic annual ruderal plant and native to Northern America, but now also spreading across Europe. Air pollution and climate change will not only affect plant growth, pollen production and duration of the whole pollen season, but also the amount of allergenic encoding transcripts and proteins of the pollen. The objective of this study was to get a better understanding of transcriptional changes in ragweed pollen upon NO2 and O3 fumigation. This will also contribute to a systems biology approach to understand the reaction of the allergenic pollen to air pollution and climate change. Ragweed plants were grown in climate chambers under controlled conditions and fumigated with enhanced levels of NO2 and O3 . Illumina sequencing and de novo assembly revealed significant differentially expressed transcripts, belonging to different gene ontology (GO) terms that were grouped into biological process and molecular function. Transcript levels of the known Amb a ragweed encoding allergens were clearly up-regulated under elevated NO2, whereas the amount of allergen encoding transcripts was more variable under elevated O3 conditions. Moreover transcripts encoding allergen known from other plants could be identified. The transcriptional changes in ragweed pollen upon elevated NO2 fumigation indicates that air pollution will alter the transcriptome of the pollen. The changed levels of allergenic encoding transcripts may have an influence on the total allergenic potential of ragweed pollen. Graphical abstract: Highlights: NO2 /O3 treatment of ragweed resulted in a differently expressed pollen transcriptome. Transcripts could be categorized in different gene ontology terms. NO2 fumigation enhanced Amb a allergen encoding transcripts of the pollen. O3 fumigation of ragweed plants did not show this clear effect. Transcripts with homology to allergens known from other plants could be identified. Abstract : Air pollution strongly affected the pollen transcriptome of ragweed, including also encoding Amb a, as well as encoding allergens known in other plants.